(untitled) (Innovative technologies, 2026)
The article presents the influence of wind-generated waves on the reshaping of the shoreline slope. To study this process, experimental investigations were carried out under laboratory conditions, and data from other researchers were also processed. Each author proposes their own methodology based on the data obtained from experiments. It is considered that the models reviewed are relatively diverse and can be used, in a generalized way, for a qualitative assessment of shoreline evolution. Based on the analysis of experimental studies and the research of other authors, a new generalized method is proposed for calculating the reshaping of reservoir shoreline profiles under the influence of wind-generated waves. It is noted that this method is recommended for wind speeds over water bodies below 20 m/s.